THE OPTIMUM LEVEL OF MELD TO MINIMIZE THE MORTALITY ON LIVER TRANSPLANTATION WAITING LIST, AND LIVER TRANSPLANTED PATIENT IN SÃO PAULO STATE, BRAZIL - Eleazar CHAIB; João Luiz Erbs PESSOA; Claudio José STRUCHINER; Luiz Augusto Carneiro D’ALBUQUERQUE; Eduardo MASSAD (ABCD: Arquivos Brasileiros de Cirurgia Digestiva, 2023)
ABSTRACT BACKGROUND: After validation in multiple types of liver disease patients, the MELD score was adopted as a standard by which liver transplant candidates with end-stage liver disease were prioritized for organ allocation in the United States since 2002, and in Brazil, since 2006. AIMS: To analyze the mortality profile of patients on the liver transplant waiting list correlated to MELD score at the moment of transplantation. METHODS: This study used the data from the Secretary of Health of the São Paulo State, Brazil, which listed 22,522 patients, from 2006 (when MELD score was introduced in Brazil) until June 2009. Patients with acute hepatic failure and tumors were included as well. We also considered the mortality of both non-transplanted and transplanted patients as a function of the MELD score at presentation. RESULTS: Our model showed that the best MELD score for patients on the liver transplant waiting list associated to better results after liver transplantation was 26. CONCLUSIONS: We found that the best score for applying to liver transplant waiting list in the State of São Paulo was 26. This is the score that minimizes the mortality in both non-transplanted and liver transplanted patients.